The French media and the forging of a Franco-British alliance in the late 1930s - Hucker, Daniel (Taylor & Francis, 2017)
This article explores the interconnections between the media in France and the emergence of a Franco-British alliance on the eve of World War Two, emphasising how newspaper, radio and newsreel coverage helped mould British perceptions of France during the late-1930s. It will argue that British assessments of France, and thus France's potential value as a wartime ally, were influenced greatly by the dominant representations furnished by the media. In 1936, such representations portrayed a polarised France unworthy of British support; by 1939, they depicted a strong and united country of inestimable value to Britain. This transformation was not simply fortuitous; by the late-1930s, French politicians, conscious of the deleterious effect that media representations of a divided France was having on their country’s prestige, endeavoured to transform the media from a symptom of decadence and malaise into a weapon of unity and strength.